Twórczość i rozwój w kontekście pandemii = Creativity and development in the context of the pandemic - Seul-Michałowska, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this work is to look for the relationship between the pandemic, health and creativity. The announcement of the pandemic caused stress that became a life event. In the light of Holmes and Rahe?s theory, cumulative life events reduce physical immunity and increase susceptibility to infections. The Newman concept assumes that life events (crisis), as a result of adopting a creative attitude towards them, lead to the effective implementation of developmental tasks (faced at that moment).
Keywords: pandemia; zdrowie; adolescencja; kryzys; sztuka; pandemic; health; adolescence; crisis; art